2008
DOI: 10.1016/j.biomaterials.2008.05.031
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo murine model of continuous intramedullary infusion of polyethylene particles

Abstract: Wear debris affects both initial osseointegration and subsequent bone remodeling of total joint replacements (TJRs). To study the complex cascade associated with the continuous generation of particles, a robust animal model is essential. To date, an animal model that incorporates continuously delivered particles to an intramedullary orthopaedic implant has not been available. In this study, we successfully infused clinically relevant ultra high molecular weight polyethylene particles, previously isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…A study has compared the two approaches in mice and shown successful delivery of 10 L volumes of 10% PMMA particles into the femoral canal, confirmed subsequently by micro-CT imaging (Zilber et al, 2008). The efficiency of this in vivo particle infusion system has been determined in a series of studies (Ortiz et al, 2008a(Ortiz et al, , 2008bMa et al, 2008Ma et al, , 2009a. In this series, the Alzet miniosmotic pump delivered UHMWPE and polystyrene particles (0.5 ± 0.015 m) over 4 weeks into an ex vivo collection tube.…”
Section: In Vivo Experimentation Methodsmentioning
confidence: 99%
“…A study has compared the two approaches in mice and shown successful delivery of 10 L volumes of 10% PMMA particles into the femoral canal, confirmed subsequently by micro-CT imaging (Zilber et al, 2008). The efficiency of this in vivo particle infusion system has been determined in a series of studies (Ortiz et al, 2008a(Ortiz et al, , 2008bMa et al, 2008Ma et al, , 2009a. In this series, the Alzet miniosmotic pump delivered UHMWPE and polystyrene particles (0.5 ± 0.015 m) over 4 weeks into an ex vivo collection tube.…”
Section: In Vivo Experimentation Methodsmentioning
confidence: 99%
“…The murine macrophage cell line RAW264.7 was transfected with the lentiviral vector to express the bioluminescent optical reporter gene, firefly luciferase (fluc), and a fluorescence reporter gene, green fluorescent protein (gfp), as previously described [7]. Prior power analysis was based on published data using a similar experimental design [25]. To detect a difference of 1.5 standard deviations from the mean for BLI and bone mineral density (BMD) with a power of 80% (a = 0.05, b = 0.20), nine animals would be needed in each group.…”
Section: Methodsmentioning
confidence: 99%
“…We strictly followed Stanford University's guidelines for the care and use of laboratory animals. The murine continuous femoral intramedullary infusion model used in this study was modified from a previously described rat model [22] and validated by successfully pumping UHMWPE and blue polystyrene particles into murine femoral medullary canals [25,31,32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure was adapted from a previously described rat model 31 and has been validated. 32,33 The animals were anesthetized using 3%-5% isoflurane in 100% oxygen and kept on a warm, sterile small animal surgery station. A medial parapatellar incision was made and the medullary cavity was exposed via the intercondylar notch of the distal left femur.…”
Section: Surgical Proceduresmentioning
confidence: 99%